Advertisement in Medical Journal – To Be or Not To Be! - Basnet, Nabin (Nepalese Medical Journal, 2018)
Medical journals are unbiased and reliable sources of information. They disseminate knowledge to educate medical practitioners and scientists of new development in different fields of medical science. The state of research and publication in developing countries is primitive, and those that are done fail to compete to be published in reputed international journals. The regional open access journals provide an opportunity to such researchers in disseminating their work. Their work is then recorded and available for other researchers and practitioners for reference. Open access journals are good platform, but it is a tremendous task for journals to survive with the little or no resource. Common sources of revenue are sales of print version and article publication charges which are often inadequate. Survival is hard and journals have to look for other sources such as individual donations and fund from institutions or medical societies. One of such journal is PloS Medicine, which has a reputable presence. These alternative sources of income may not be available for all journals and have to turn to advertisements as a major source of revenue. Even some of the reputed traditional, subscription-based journals put advertisements as their reliable source of income.